The Calculation of Fault Slip Rate as a Necessary Tool for City Planning near Active Faults. A Case Study from the Coastal Area of Heraklion, Crete - Papanikolaou, D.; Vassilakis, Emm.; K. Valadaki; Zacharias, N.; I. Maniatis (3rd Hell. Conf. on Earthquake Engineering & Technical Seismology, 2008)
The city planning of Heraklion in Crete included the construction of the new Courthouse building at the eastern part of the town where several active fault have been mapped during an earlier microzonation study. The significance of the new building required detailed studies for the exact tracing of the faults and the period of their latest activation. The proposed methodology included trenching across the fault traces which are either controlling a morphological discontinuity or covered by human activities. Sampling for radiocarbon and optical luminance dating was carried out aiming for the exact age of the ruptured strata by the active faults. The combination of the described methodologies resulted the modification of the city plan, as constructions were designed to be built on the fault trace.